2008
DOI: 10.1362/026725708x273975
|View full text |Cite
|
Sign up to set email alerts
|

The blind spot of relationships in consumer markets: the consumer proneness to engage in relationships

Abstract: This paper looks at the nature of relationships between consumers and firms, developing a dyadic conceptual model for consumer markets where both parties are taken into consideration. We question whether a relationship is necessarily the preferred state from the customer's perspective or if this is only in the mind of the seller. This topic appears to remain the blind spot of relationships in consumer markets. The empirical data is gathered from interviews and focus group discussions embedded in three cases fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 41 publications
(37 reference statements)
1
13
0
Order By: Relevance
“…Bloemer and Odekerken-Schröder's (2006) research conducted in a bank setting have asserted that, employee relationship proneness is an antecedent of affective and normative commitment that leads to behavioral loyalty, and then it also results in positive word-of-mouth. Fernandes and Proença (2008) have claimed that consumer proneness is a driver of buyer-seller relationships in B2C markets by their research conducted in a service setting. The case studies in Fernandes and Proença's (2008) research have revealed that consumers differ in having desires to engage in service providers' activities due to their different relationship proneness levels.…”
Section: Effects Of Relationship Pronenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Bloemer and Odekerken-Schröder's (2006) research conducted in a bank setting have asserted that, employee relationship proneness is an antecedent of affective and normative commitment that leads to behavioral loyalty, and then it also results in positive word-of-mouth. Fernandes and Proença (2008) have claimed that consumer proneness is a driver of buyer-seller relationships in B2C markets by their research conducted in a service setting. The case studies in Fernandes and Proença's (2008) research have revealed that consumers differ in having desires to engage in service providers' activities due to their different relationship proneness levels.…”
Section: Effects Of Relationship Pronenessmentioning
confidence: 99%
“…Fernandes and Proença (2008) have claimed that consumer proneness is a driver of buyer-seller relationships in B2C markets by their research conducted in a service setting. The case studies in Fernandes and Proença's (2008) research have revealed that consumers differ in having desires to engage in service providers' activities due to their different relationship proneness levels. Some consumers do not purchase from the same provider since service providers does not seem to offer more value to them to make them loyal.…”
Section: Effects Of Relationship Pronenessmentioning
confidence: 99%
“…RM theorists have advocated the benefits of RM for consumer marketing using a range of criteria (Bagozzi, 1995; Sheth and Parvatiyar, 1995a), some of which stress consumer benefits and others the benefits to organizations. Some critics have argued that consumers are often unenthusiastic about the prospect of deeper relationships with commercial partners (Fitchett, 2005; Badot and Cova, 2008; Fernandes and Proenca, 2008). The rhetoric of RM can mask less benign corporate intentions (Fitchett and McDonagh, 2000; O'Malley and Tynan, 2000), and RM offers little to consumers and firms other than window dressing, increased costs of operation and an erosion of trust (O’Malley and Prothero, 2004).…”
Section: Critiques Of Relationship Marketingmentioning
confidence: 99%
“…There is also an inability to universally apply the theory to the business environment, as not all organisations value relationships at all times; it is also suggested that the value of transactional marketing should not be underestimated or totally removed from marketing strategies ( M ö ller and Halinen, 2000 ;Hui, 2006 ;Fernandes and Proen ç a, 2008 ;Gummesson, 2008 ). Despite the criticisms of RM, it is highly evident that stakeholder relationships are the basis of the successful event and that RM is valuable in relation to the festival industry ( Fuan and Nicholls, 2000 ;Collin-Lachaud and Duyck, 2002 ).…”
Section: Literature Reviewmentioning
confidence: 99%